2007
DOI: 10.1088/0031-9155/52/8/005
|View full text |Cite
|
Sign up to set email alerts
|

In vivostudy of an x-ray fluorescence system to detect bone strontium non-invasively

Abstract: An x-ray fluorescence (XRF) system using 125I as the source was developed to measure strontium in bone in vivo. As part of an in vivo pilot study, 22 people were measured at two bone sites, namely the index finger and the tibial ankle joint. Ultrasound measurements were used to obtain the soft tissue thickness at each site, which was necessary to correct the signal for tissue attenuation. For all 22 people, the strontium peak was clearly distinguishable from the background, proving that the system is able to m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 31 publications
(45 reference statements)
2
66
2
1
Order By: Relevance
“…In the second pilot study, with the improved system [45] it was possible to detect strontium in all 22 volunteers. Measurements were made in both fingers (predominantly cortical) and ankles (predominantly trabecular).…”
Section: Results Of the Pilot Study Of Bone Strontiummentioning
confidence: 99%
See 1 more Smart Citation
“…In the second pilot study, with the improved system [45] it was possible to detect strontium in all 22 volunteers. Measurements were made in both fingers (predominantly cortical) and ankles (predominantly trabecular).…”
Section: Results Of the Pilot Study Of Bone Strontiummentioning
confidence: 99%
“…However, neither of these initiatives were followed up in the respective laboratories. Zamburlini et al [45] improved their system very considerably enhancing its performance, so that it was possible to measure the strontium X-ray signal in all subjects who participated in their study.…”
Section: In Vivo X-ray Fluorescence Of Bone Strontiummentioning
confidence: 99%
“…Measurements were made at two sites, finger and ankle. Sr was clearly detectable in all 22 subjects who participated in the study 45) . There was a strong correlation between finger Sr and ankle Sr in these subjects, which confirmed that the method can distinguish with confidence between different levels of Sr in different subjects and that Sr levels were similar in these two different bones, supporting those literature reports that claim that Sr is approximately uniformly distributed in the different bones in the body 47) .…”
Section: Strontium In Bonementioning
confidence: 89%
“…Neither of these systems appears to be in current use, although the latter, which used the Ag x-rays from a 109 Cd source, is similar to one of the systems developed and used more recently. In fact a second radioisotope source, 125 I, has also been used and it is the 125 I which results in somewhat better system performance, although either source is definitely usable 45) . In the present system at McMaster, a source of 125 I is mounted coaxially with and in front of a Si(Li) detector which has a 16mm diameter and 7mm thickness.…”
Section: Strontium In Bonementioning
confidence: 99%
“…O resultado desta movimentação de elétrons é a emissão, na forma de fóton de raios-x, de energia característica e bem definida para cada elemento constituinte da amostra. Este efeito é esquematizado no diagrama da figura 1 (Zamburlini et al, 2007;Carvalho et al, 2009). …”
Section: Parâmetros Obtidos Através De Ensaios Clássicos Deunclassified